EFEKTIFITAS PEMBERIAN JUS JAMBU BIJI TERHADAP KADAR KOLESTEROL TOTAL PADA PRALANSIA OVERWEIGHT - Rufaida Rosyida; Yuniarti Yuniarti; Sri Noor Mintarsih; Ria Ambarwati; Meirina Dwi Larasati (JURNAL RISET GIZI, 2018)
Background : Cholesterol one of the causes of heart disease that is more risky in overweight society. Corner heart disease cases in Semarang city caused by high cholesterol levels as much as 53%. Screening results in overweight elderly in the Bendan Duwur urban area was 29.25%. Efforts in lowering cholesterol is a high-fiber diet with one of the guava fruit. Objective: To know the effectiveness of giving guava juice to cholesterol levels. Method: This research type used quasi experiment design with early and last test group design. The subjects were had with simple random sampling obtained as many as 21 people divided equally in two treatment groups and one control.Guava juice of 200 grams / 100 ml for the first treatment group and 150 g / 100 ml for the second treatment group was given twice daily for 14 days. Cholesterol was got by blood test (strip-test). Analysis used multivariate test with Anova Repeated Measure. Results: There was a significant effect on guava juice on the decrease of cholesterol (p 0,04) and there was a difference in the decrease among treatment group that was 9,92 mg/dl. There was no significant effect of fat intake (p 0,994), carbohydrate intake (p 0,888) and level of physical activity (p 0,136) on cholesterol level. Conclusion: Guava juice dose of 150 grams / 100 ml of water is more effective in lowering total cholesterol levels.